Kelimpahan Dan Keragaman Serangga OPT (Organisme Pengganggu Tanaman) dan Musuh Alaminya pada Tanaman Jagung dan Padi dengan Sistem Rotasi Tanaman - Ervianna, Ana Rita; Hadi, Mochamad; Rahadian, Rully (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Insects in agricultural ecosystem can play a role as pests or natural enemies. The abundance and diversity of insect pests and natural enemies are interconnected because insect pests are food for natural enemy insects. The aims of the study were to compare the abundance and diversity of pest insects and natural enemies of corn and rice plant, and to determine the similarity of pest insects and natural enemies of corn and rice plant using crop rotation systems. The sampling has performed four times i.e, in the vegetative phase of corn, generative corn, vegetative rice, and generative rice. The sampling method used sweep net method. The results showed that the number of individual pest insects and natural enemies of each growth phase of corn plants were lower than rice plants. The number of species pest insect and natural enemies of each growth phase of corn plants were lower than rice plants. In addition the diversity of pest insect of each growth phase of corn plants was higher than rice plants while the diversity of natural enemies in each growth phase of corn plants was lower than rice plants. The diversity index of pest insects and natural enemies of each growth phase in corn plants and rice plants was in the medium category. The presence of pest insects andÂ natural enemies in each growth phase of corn and rice plants shows the species in the two compared ecosystems were different.